Formulation and Physical Evaluation of Lavender (Lavandula angustifolia) Essential Oil Aromatherapy Candles - Tri Sucianita T. Tama; Nurain Thomas; Ariani H. Hutuba; Mohamad Adam Mustapa (Jurnal Literasi Mandiri, 2026)
Lavender flowers are widely used in aromatherapy because their principal constituents, linalyl acetate and linalool, are associated with relaxing effects. Aromatherapy preparations contain volatile aromatic substances intended to promote calmness and relaxation. This study aimed to formulate and physically evaluate aromatherapy candles containing lavender (Lavandula angustifolia) essential oil. An experimental laboratory design was employed, with lavender essential oil as the active ingredient and variations in beeswax and stearic acid concentrations. Formula I contained 50% soy wax, 50% beeswax, and 25% stearic acid, whereas Formula II contained 50% soy wax, 60% beeswax, and 30% stearic acid. The formulations were evaluated for organoleptic characteristics, burning performance, melting point, and hedonic acceptance. Both formulations met the specified physical-evaluation criteria, demonstrating that lavender essential oil can be successfully incorporated into aromatherapy candle formulations